Fuzzy optimization of geometrical nonlinear space truss design - Keleşo?lu, Ömer; Ülker, Mehmet (My University, 2005)
This paper presents a general algorithm for nonlinear space truss system optimization with fuzzy constraints and fuzzy parameters. The analysis of the space truss system is performed with the ANSYS program. The algorithm of multiobjective fuzzy optimization techniques was formed with ANSYS parametric dimensional language. In the formulation of the design problem, weight and minimum displacement are considered the objective functions. Three design examples are presented to demonstrate the application of the algorithm. © Tübi?tak.
Keywords: ANSYS; Fuzzy optimization; Fuzzy sets; Membership function; Multiobjective; Nonlinear space truss